2000
DOI: 10.1016/s0022-5347(05)67646-x
|View full text |Cite
|
Sign up to set email alerts
|

Complexed Prostate Specific Antigen Provides Significant Enhancement of Specificity Compared With Total Prostate Specific Antigen for Detecting Prostate Cancer

Abstract: The measurement of complexed PSA represents an alternative to the use of percent free PSA, although the patient populations identified by the 2 tests are different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(44 citation statements)
references
References 20 publications
3
38
0
3
Order By: Relevance
“…Areas under the ROC curve have been reported to range from 0.65 to 0.77 in case series comprised of patients enrolled in screening trials [4,19-21] or followed in urologic practice [22]. Among urologic studies, we found only Labrie and colleagues reporting a substantially higher area under the ROC curve: 0.88 (SE 0.03) [23].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Areas under the ROC curve have been reported to range from 0.65 to 0.77 in case series comprised of patients enrolled in screening trials [4,19-21] or followed in urologic practice [22]. Among urologic studies, we found only Labrie and colleagues reporting a substantially higher area under the ROC curve: 0.88 (SE 0.03) [23].…”
Section: Discussionmentioning
confidence: 79%
“…In the urologic literature, sensitivities ranged from 67% to 90%, specificities ranged from 28% to 59%, and positive predictive values ranged from 30% to 43% [9-11,19,20,27,28]. However, almost all of the published studies, including our own, are flawed by potential work-up bias because men with elevated PSA levels were significantly more likely to be biopsied.…”
Section: Discussionmentioning
confidence: 87%
“…Kehinde et al [18] reported that only 18 (11.0%) of the 161 patients with PSA 10.0 ng/ml or greater were diagnosed with PC, and 33 (21.0%) of the patients were diagnosed with of prostatitis. Several PSA-related factors, including the f/t PSA, PSAD, and PSA velocity, have been examined in an attempt to improve the efficiency of prostate biopsies in patients who are within the PSA ''gray zone'' [19,20]. Karazanashvili and Managadze [6] reported that using the percentage of PSA change after antibacterial therapy improved the PC detection accuracy in chronic prostatitis patients with a baseline PSA of 4.0-10.0 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these theoretical advantages initial retrospective reports of the use of ACT complexed PSA showed no improvement in specificity compared to the use of the f/t PSA ratio. 36 Indeed one study surprisingly reported it to be of decreased utility. 37 Recently a prospective study has been reported and though the numbers were small (only 51 men with cancer) ACT complexed PSA did outperform f/t PSA ratio with a specificity of 24.8% compared with 17.4%, although this was not statistically significant.…”
Section: Methods Based On the Serum Distribution Of Psamentioning
confidence: 99%